Public insurance in private medical markets : some problems of national health insurance - Frech, H. E.; Ginsburg, Paul B. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1978)
The original/previous paper compared various methods of fee or price regulation in medical care and different mechanisms for consumer copayment. In recasting the paper for a new audience, the authors discovered that a comprehensive treatment of the policy issues involved in designing benefits under national health insurance required a broader approach. As a consequence, three major topics not addressed in the original paper were added: a discussion of the general problem of public insurance in private markets (chapter 2), an examination of the health maintenance organization as an innovation for dealing with problems inherent in third-party market relationships (chapter 5), and a discussion of policy alternatives (chapter 6). Also, a discussion of the appropriateness of economic analysis for dealing with issues of medical care resource allocation (Appendix A) has been included.
A revision and expansion of the authors' paper originally published in economic inquiry, v. 13, no. 1 (March 1975)
Includes bibliographical references.
ne 09/05/2018
Loans
Keywords: Insurance; Health; United States